Rasuah dalam karya sastera Melayu klasik: Satu analisis semantik kognitif - Nor Hashimah Jalaluddin,; Rozaimah Rashidin, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
Syed Hussein Alatas has given seven typologies of corruption namely, nepotism, investive, defensive, transactive, autogenic, blackmail and supportive. The typologies listed are based on personal observation. This article attempts to formalize these corruption typologies using a cognitive semantics approach. Based on the classical literary works such as Sejarah Melayu, Hikayat Hang Tuah, Hikayat Terung Pipit and Hikayat Raja Pasai, the concept of corruption will be explicated. The meaning extension of corruption in Malay can be divided into core meaning, peripheral meaning and sub-peripheral meaning. Cognitive mechanisms, especially the conceptual metaphor such as container schema, force schema, link schema, and hierarchical schema are utilized in explaining the corruption typologies in depth. Subsequently, this article attempts to relate the phenomena of corruption with contemporary Malay mind. The perception of ‘membalas budi’ (to pay back in return) has made the concept of corruption ambiguous, in fact ‘halal’ (permissible) in the eyes of the Malays